Social Networks in Improving the Learning Achievement of Zoning Pathway Students - Eka Dewi, Kartika Purnama; Nurhadi, Nurhadi; Zuhri, Saifuddin (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
Zoning policies create associations of students with different academic abilities and school backgrounds. The focus of this research is on zonal pathway students who have experienced improvements in terms of cognitive aspects and explains the problem of social networks in increasing the grades of zonal pathway students. This research uses a descriptive qualitative approach to examine the issues raised. The research subjects were determined using a purposive sampling technique, namely 12th-grade MIPA students. The research results explain that students have similar social network patterns among each other. Increasing student learning outcomes is dominated by peer group interaction within and outside the school environment. In this way, peers trigger or motivate students to improve learning outcomes.